2008
DOI: 10.1063/1.2937403
|View full text |Cite
|
Sign up to set email alerts
|

Efficient deep-blue phosphorescent organic light-emitting device with improved electron and exciton confinement

Abstract: We report a significant improvement in the efficiency of deep-blue phosphorescent organic light-emitting devices based on the electrophosphorescent dye bis(4′,6′-difluorophenylpyridinato)tetrakis (1-pyrazolyl) borate (FIr6). Using 1,1-bis[(di-4-tolylamino)phenyl]cyclohexane (TAPC) as the hole transport layer (HTL), we achieved a maximum external quantum efficiency of ηEQE=(18±1)%, which is approximately 50% higher than ηEQE=12% in a previously reported device with bis[N-(1-naphthyl)-N-phenyl-amino]biphenyl as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
130
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(132 citation statements)
references
References 14 publications
1
130
0
1
Order By: Relevance
“…[ 19 , 24 ] The power effi ciency of DEL device 1 was better than that of the POLED using UGH2, [ 19 ] where the fi lm thickness of the emitting layer is almost the same as that of DEL device 1. Moreover, the power effi ciency and turn-on voltage of DEL device 1 are comparable to those previously reported for a DEL-structured POLED with a p-i-n structure by Eom et al [ 24 ] The emittinglayer material in almost all previously reported FIr6-based POLEDs was the poor electron-transporting material UGH2, which resulted in a high driving voltage.…”
Section: Methodsmentioning
confidence: 99%
“…[ 19 , 24 ] The power effi ciency of DEL device 1 was better than that of the POLED using UGH2, [ 19 ] where the fi lm thickness of the emitting layer is almost the same as that of DEL device 1. Moreover, the power effi ciency and turn-on voltage of DEL device 1 are comparable to those previously reported for a DEL-structured POLED with a p-i-n structure by Eom et al [ 24 ] The emittinglayer material in almost all previously reported FIr6-based POLEDs was the poor electron-transporting material UGH2, which resulted in a high driving voltage.…”
Section: Methodsmentioning
confidence: 99%
“…17 The respective transparent electrodes (ITO for bottom-emitting devices and the oxide/metal/oxide trilayer for top-emitting devices) were used as the anodes, whereas a Cs 2 CO 3 interlayer 18 and Al were used as the cathode. Phosphorescent devices consisted of a p-i-n structure with MeO-TPD doped with F 4 -TCNQ as the HIL, 1,1-bis-(di-4-tolylaminophenyl)cyclohexane (TAPS) 19 as the HTL, N,N -dicarbazolyl-3,5-benzene (mCP) 19 doped with 10 wt. % fac tris(2-phenylpyridine) iridium (Ir(ppy) 3 ) green phosphorescent dopant as the EML, 20 4,7-diphenyl-1,10-phenanthroline (BPhen) as ETL and BPhen doped with CsCO 3 electron injection layer.…”
Section: Methodsmentioning
confidence: 99%
“…It should be pointed out that the EL spectra of device B is still shifted slightly, which is thought to be the exciton density distributes in mCP host layer and 3TPYMB host not evenly, while it was improved in device C by using host TAPC replace mCP because of the better hole transporting and excitons blocking function of TAPC. 18,19 Therefore, keeping the exciton distribution uniform in EML is essential, which mainly depends on the selection of host for each EML. The host should have appropriate band gap to get effective energy transfer to dopant, as list in Table I, also appropriate charge transporting function to balance the electron and hole dispersed in whole EML.…”
Section: Discussion On Luminous Mechanismmentioning
confidence: 99%
“…Here, from a statistics on charge mobility, a rule is indicated that the electron mobility and hole mobility alter inconsistent according to electric field in organic materials, and electron mobility rises faster than that of holes, [14][15][16][17] which result in that electron transport rate rises faster than that of holes with the increases of driving voltage. 18 So the exciton recombination zone will shift from the ETL (electron transporting layer) side to the HTL(hole transporting layer) side. 11,19 For a stacked multi-layer white-light PhOLED, such a shift of exciton recombination zone will change the ratio of primary emission, inducing in a poor color stability.…”
Section: Introductionmentioning
confidence: 99%